2017
DOI: 10.1002/jso.24675
|View full text |Cite
|
Sign up to set email alerts
|

SLNB in cutaneous SCC: A review of the current state of literature and the direction for the future

Abstract: The concept of the sentinel lymph node biopsy (SLNB) has been universally accepted for melanoma, however, remains controversial for squamous cell carcinoma (SCC). We performed a quantitative review on 260 cases of SCC that had a SLNB. The positivity rate was found to be 14.6%. Literature was qualitatively reviewed to determine whether a positive SLNB has any bearing on prognosis in SCC cases, finding a significant relationship between poor prognosis and a positive SLN (P = 0.0082).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 58 publications
(117 reference statements)
3
16
0
6
Order By: Relevance
“…To our knowledge, this is the second largest ever published series concerning SLNB and non-ano-genital highrisk cSCC. Its positivity rate of 11.6% (n = 8) is consistent with the latest literature reviews, reporting rates ranging from 8% (22) to 14.6% (17). The largest series by Wu et al (18) included 83 patients, but only 5 SLNB were positive (6%).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…To our knowledge, this is the second largest ever published series concerning SLNB and non-ano-genital highrisk cSCC. Its positivity rate of 11.6% (n = 8) is consistent with the latest literature reviews, reporting rates ranging from 8% (22) to 14.6% (17). The largest series by Wu et al (18) included 83 patients, but only 5 SLNB were positive (6%).…”
Section: Discussionsupporting
confidence: 81%
“…On the one hand, there is no data to confirm that diagnosis of microscopic lymph node metastasis in cSCC leads to a better prognosis than later diagnosis (22,23). On the other hand, a literature review of 260 procedures taken from 14 studies (17) revealed that patients with confirmed subclinical node metastasis still had a significantly higher mortality rate than SLNB-negative patients (p = 0.008), despite appropriate adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most patients diagnosed with CSCC have a good prognosis, a few cases in the high-risk group with the criteria of poor diagnosis have an aggressive clinical course and higher rates of local recurrence and metastasis (5,(9)(10)(11)(12). Risk factors defined by AJCC are shown in Table 2 An important point to be noted in our study was that the presence of PNI (n:2) was detected in all CSCC patients with a diameter > 2 cm.…”
Section: Discussionmentioning
confidence: 53%
“…The lymph node in the body region to which a malignant tumor first drains is named as sentinel lymph node (SLN). This is the first lymphoid target where tumors reach for the first time via lymphatic route (4,(7)(8)(9)(10)(11)(12)(13). The importance of SLN sampling in identification of the occult lymph node metastases has been established, and accepted as a prognostic factor (14).…”
Section: Introductionmentioning
confidence: 99%